2005
DOI: 10.1095/biolreprod.104.032003
|View full text |Cite
|
Sign up to set email alerts
|

Follicle-Stimulating Hormone Affects Metaphase I Chromosome Alignment and Increases Aneuploidy in Mouse Oocytes Matured in Vitro1

Abstract: Follicle-Stimulating Hormone (FSH) at a wide range of doses is routinely added to culture media during in vitro maturation (IVM) of oocytes, but the effects on oocyte health are unclear. The suggestion that superovulation may cause aneuploidy and fetal abnormalities prompted us to study the potential role of FSH in the genesis of chromosomal abnormalities during meiosis I. Mouse cumulus-oocyte complexes (COCs) isolated from the antral follicles of unprimed, sexually immature B6CBF1 mice were cultured in increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
98
2
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 155 publications
(107 citation statements)
references
References 78 publications
6
98
2
1
Order By: Relevance
“…There is growing evidence in animal studies to support the hypothesis that elevated FSH is an underlying cause of embryo defects [9,10,39]. However, whereas animal studies seem to support an association between FSH exposure and embryonic defects, human studies have been more inconsistent [25,26,31,37,45]. In our study, the FSH dose and the number of retrieved oocytes had a negative impact on the TE quality.…”
Section: Discussioncontrasting
confidence: 54%
“…There is growing evidence in animal studies to support the hypothesis that elevated FSH is an underlying cause of embryo defects [9,10,39]. However, whereas animal studies seem to support an association between FSH exposure and embryonic defects, human studies have been more inconsistent [25,26,31,37,45]. In our study, the FSH dose and the number of retrieved oocytes had a negative impact on the TE quality.…”
Section: Discussioncontrasting
confidence: 54%
“…In previous studies that reported a low frequency of aneuploidy, one-cell zygotes were obtained from mated females: thus, they underwent meiotic maturation and fertilization in vivo (16,26). However, several studies have shown that when GV-stage oocytes are matured to the MII stage in vitro, aneuploidy is observed in 11-33% of them (27)(28)(29). Moreover, Fraser and Maudlin (16) reported an increased incidence of aneuploidy (Ï·4.3%) in one-cell zygotes fertilized in vitro compared with those fertilized in vivo (Ï·1.5%).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, when compared to zygotes derived from spontaneous ovulation, mouse zygotes obtained after ovarian stimulation showed an increased rate of chromosomal aberrations in the female pronucleus and compromised embryo development (Vogel & Spielmann 1992). Likewise, in vitro-matured mouse oocytes exposed to high concentrations of FSH showed accelerated nuclear maturation and increased aneuploidy (Roberts et al 2005).…”
Section: Does Ovarian Stimulation Disrupt Chromosomal Competence Of Tmentioning
confidence: 99%